2010
DOI: 10.1017/s1431927610000358
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Fractal Analysis of Shape in Cancer Cells Treated with Combinations of Microtubule-Polymerizing and -Depolymerizing Agents

Abstract: The current prognostic parameters, including tumor volume, biochemistry, or immunohistochemistry, are not sufficient to reflect the properties of cancer cells that distinguish them from normal cells. Our focus is to evaluate the effects of a combination of microtubule-polymerizing Taxol and -depolymerizing colchicine on IAR20 PC1 liver cells by measuring the surface fractal dimension as a descriptor of two-dimensional vascular geometrical complexity. The fractal dimension offers a rapid means of assessing cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…can be characterized by fractal analysis by using two statistical measures known as the fractal dimension ( D F ) and lacunarity ( λ ). Image analysis that employs the use of fractals has been used in many areas (Jelinek & Fernandez, 1998; Yaşar & Akgünlü, 2005; Al-Kadi & Watson, 2008; Updike & Nowzari, 2008; Uppal et al, 2010; Karperien et al, 2013), including image segmentation (Dubuisson & Dubes, 1994; Keller et al, 1989) and the classification of ecological (Kenkel & Walker, 1993; Malhi & Román-Cuesta, 2008) and urban (Myint & Lam, 2005) spatial distributions.
Figure 1 a: Koch snowflake. b: Schematic demonstrating the gliding box-counting algorithm for the lacunarity analysis of a binary image of size M .
…”
Section: Introductionmentioning
confidence: 99%
“…can be characterized by fractal analysis by using two statistical measures known as the fractal dimension ( D F ) and lacunarity ( λ ). Image analysis that employs the use of fractals has been used in many areas (Jelinek & Fernandez, 1998; Yaşar & Akgünlü, 2005; Al-Kadi & Watson, 2008; Updike & Nowzari, 2008; Uppal et al, 2010; Karperien et al, 2013), including image segmentation (Dubuisson & Dubes, 1994; Keller et al, 1989) and the classification of ecological (Kenkel & Walker, 1993; Malhi & Román-Cuesta, 2008) and urban (Myint & Lam, 2005) spatial distributions.
Figure 1 a: Koch snowflake. b: Schematic demonstrating the gliding box-counting algorithm for the lacunarity analysis of a binary image of size M .
…”
Section: Introductionmentioning
confidence: 99%
“…He reported that FD values are significantly different for each TNM stage, thus validating the method as a tool for cancer stadialization (19). Uppal et al showed the correlations of fractal dimensions of cell contours with the latent factors (20).…”
Section: Discussionmentioning
confidence: 98%
“…Fractal analysis measures the complexity of geometric structures. The fractal dimension offers a rapid means of assessing cell shape analysis (16). Many analytical methods have been proposed to determine the fractal dimension of natural objects.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed that these changes, though not so obvious, occur much early during cell structural reorganization induced by UV light exposure. It is known that cell surface roughness and shape have a substantial impact on cell fractal characteristics and cytoplasm FD is particularly known to be influenced not only by heterogeneity of the image, but also by irregularities detected on an object’s surface (Uppal et al, 2010; Wang et al, 2010; Dokukin et al, 2011). Unlike lacunarity, which is firmly related to the gappiness of image texture, FD values are more likely to be influenced by border pixels of the image ROI.…”
Section: Discussionmentioning
confidence: 99%